A Primer to (Cross-Cultural) Multi-Group Invariance Testing Possibilities in R - Fischer, Ronald; Karl, Johannes A. (Frontiers in Psychology, 2019)
Psychology has become less WEIRD in recent years, marking progress towards becoming a truly global psychology. However, this increase in cultural diversity is not matched by greater attention to cultural biases in research. A significant challenge in culture-comparative research in psychology is that any comparisons are open to possible item bias and non-invariance. Unfortunately, many psychologists are not aware of problems and their implications, and do not know how to best test for invariance in their data. We provide a general introduction to invariance testing and a tutorial of three major classes of techniques that can be easily implemented in the free software and statistical language R. Specifically, we describe 1) confirmatory and multi-group confirmatory factor analysis, with extension to exploratory structural equation modelling, and multi-group alignment; 2) iterative hybrid logistic regression as well as 3) exploratory factor analysis and principal component analysis with Procrustes rotation. We pay specific attention to effect size measures of item biases and differential item function. Code in R is provided in the main text and online (see https://osf.io/agr5e/), and more extended code and a general introduction to R are available in the supplementary materials.